Optimization of TikTok Use as a Medium for Digital Literacy-Based Learning Outcomes in Elementary Schools - Kurniawan, Diki; Heryani, Rina; Agustin, Mubiar (International Conference on Elementary Education, 2025)
This study investigates the use of TikTok as a tool to enhance digital literacy in elementary school students. Using a one-group posttest-only design and incorporating the RADEC (Read, Answer, Discuss, Explain, Create) model, the research explored how students transformed their understanding of the topic